Informing the Government of South Africa’s projections on the economic effects of the COVID-19 pandemic - CGIAR Research Program on Policies, Institutions, and Markets (2020)
Research on the impact of the initial nationwide COVID-19 lockdown on the South African economy carried out by an IFPRI-led team under the banner of the Southern Africa-Towards Inclusive Economic Development (SA-TIED) program informed the Government of South Africa’s projections on the economic effects of the pandemic and was used by the South African Reserve Bank and National Treasury to adjust their macroeconomic forecasts.